Lorenz-based chaotic secure communication schemes (2012)
Secure communication systems employing chaos have recently attracted significant interest. This is partly due to their high unpredictability and simplicity of implementation over conventional secure communications systems. This study presents the implementation of four chaotic modulation techniques employing Lorenz system as chaos generator. The techniques are Chaotic Masking (CM), Chaos Shift Keying (CSK), Chaos On-Off Keying (COOK), and Differential Chaos Shift Keying (DCSK). Simulations were carried out using Simulink in Matlab environment to implement these techniques. A qualitative evaluation of the transmitted signal waveforms in all the cases considered showed that DCSK gives the highest level of security followed by CSK while COOK gives the least level of security.